1990
DOI: 10.18174/njas.v38i3b.16569
|View full text |Cite
|
Sign up to set email alerts
|

Organic matter digestibility in horses and its prediction.

Abstract: Organic matter (OM) digestibility of 53 feeds was estimated in horses, sheep and in vitro using rumen fluid. Feeds tested were: roughages (grass hay, fresh grass, wilted grass silage, forage maize and artificially dried roughage), compound feeds and compound feed ingredients including cereals. Technical merits of the chosen procedure for digestibility trials with horses are discussed. Horse digestibility data for forages were consistently lower than sheep data, with a variable fibre level effect. For compound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…In one study, the inclusion of extruded linseed (20% in DM) in the diets of horses decreased the digestibility of nutrients compared to hay-only and hay/wheat bran diets [56]. In agreements with the results of the present study, Smolders et al [57] found increased digestibility values of the diet nutrients when horses were fed compound feed containing (16%) linseed expeller plus more digestible ingredients (cereals). In the present study, the intake of linseed groats was 6.3%-6.7% in DM, and when combined with digestible fibre sources, also improved the diet's digestibility.…”
Section: Diet Digestibilitysupporting
confidence: 91%
“…In one study, the inclusion of extruded linseed (20% in DM) in the diets of horses decreased the digestibility of nutrients compared to hay-only and hay/wheat bran diets [56]. In agreements with the results of the present study, Smolders et al [57] found increased digestibility values of the diet nutrients when horses were fed compound feed containing (16%) linseed expeller plus more digestible ingredients (cereals). In the present study, the intake of linseed groats was 6.3%-6.7% in DM, and when combined with digestible fibre sources, also improved the diet's digestibility.…”
Section: Diet Digestibilitysupporting
confidence: 91%
“…However, the higher ash content in the intestinal tract of horses on the HS diet could be the result of lower amounts of ash absorption in the intestine as a direct consequence of the high amounts of starch fed in the diet [ 31 ]. On the contrary, the higher percentage of OM found in the sternal flexure, the pelvic flexure, the right dorsal colon and the rectum in the HF group could be related to the high fibre intake which has been reported to reduce the digestibility of OM [ 32 , 33 ]. Moreover, a diet*sex interaction was found in relation to the percentage of OM and ash content in the sternal flexure.…”
Section: Discussionmentioning
confidence: 99%
“…However, haylage can be both higher and lower in energy, protein, fibre, mineral and vitamin concentration compared to hay or silage. This is due to the nutritive value of forage being primarily determined by plant maturity at harvest (Darlington & Hershberger, ; Edouard et al., ; Müller, ; Ragnarsson & Lindberg, ; Ragnarsson & Lindberg, ; Särkijärvi, Sormunen‐Cristian, Heikkilä, Rinne, & Saastamoinen, 2012; Smolders, Steg, & Hindle, ; Woodward, Nielsen, Liesman, Lavin, & Trottier, ) and not by method of conservation. Considering that DM concentration in the forage is the most dominant factor determining the type of conservation that takes place, it is logical to define silage and haylage on the basis of DM concentration.…”
Section: Defining Silage and Haylagementioning
confidence: 99%